A Pengaruh Gender dan Jenis Umpan Balik dalam Pembelajaran Matematika Berbasis Permainan Digital di Sekolah Dasar - Yulianto, Dwi; Juniawan, Egi Adha; Junaedi, Yusup (Edumatica : Jurnal Pendidikan Matematika, 2025)
This study investigates gender-based differences in learning outcomes and motivation in digital game-based mathematics instruction using the Lectora Inspire platform. The primary focus centers on the effectiveness of two types of instructional feedback, MTF and STF. The study aims to explore how gender and feedback type interact in influencing cognitive learning gains as well as motivational and perceptual dimensions, including interest, competence, autonomy, effort, pressure-free experience, and perceived value of learning activities. Employing a quasi-experimental pretest–posttest design, the study involved 81 third and fourth-grade students from three elementary schools in Jakarta, Indonesia, who were randomly assigned to either the MTF or STF group. Learning outcomes were assessed using standardized mathematics tests aligned with the national curriculum, while motivation was measured through the IMI. Two-way ANOVA and MANOVA analyses revealed that although male students scored higher on post-tests, female students demonstrated greater learning gains after controlling for pre-test scores, particularly under the STF condition. Female students also reported significantly higher motivation in the domains of interest and perceived competence, with no significant differences observed in autonomy. Furthermore, gender differences in perceptions of effort, pressure-free experience, and learning value were not statistically significant, though females showed more positive trends overall. Feedback condition alone did not significantly influence learning outcomes or student perceptions. These findings underscore the importance of incorporating gender-sensitive approaches when designing adaptive and inclusive digital feedback mechanisms in mathematics education.